Sindrom Beckwith-Wiedemann dengan Presentasi Trias Klasik pada Bayi: Sebuah Laporan Kasus - Yogi Arvendo; Ismi Citra Ismail (CV. Jasa Sukses Abadi, 2026)
Beckwith-Wiedemann syndrome (BWS) is a rare congenital overgrowth disorder and genetic imprinting disorder caused by dysregulation of chromosome 11p15.5. This disorder increases the risk of embryonal tumors, making early diagnosis crucial. This case report aims to present the clinical diagnosis of BWS based on the international consensus scoring system in an infant with a classic clinical triad. A 2-month-14-day-old male infant was admitted with a large tongue and a history of omphalocele since birth. The patient was born via cesarean section at 37 weeks of gestation with a birth weight of 3,800 grams (>90th percentile on the Lubchenco curve). The omphalocele was reported to have closed spontaneously at 1 month of age. The patient had experienced neonatal hypoglycemia following NICU care, which required glucose infusion. Physical examination revealed macroglossia, a scalp hemangioma, and right upper extremity hemihyperplasia. Laboratory examination showed an alpha-fetoprotein (AFP) level within the normal range for age (587.98 ng/mL; reference range 10–1,359 ng/mL), while echocardiography detected a small atrial septal defect (ASD). Based on the 2018 international consensus, the cumulative clinical findings yielded a score of 8, confirming a clinical diagnosis of Classic BWS. The clinical diagnosis of BWS in this patient could be strongly established using the scoring system, even though molecular genetic testing was not available or had not been performed. Given the high risk of embryonal malignancy, long-term management must include a rigorous periodic tumor surveillance protocol comprising abdominal ultrasonography and serum AFP monitoring every 3 months, along with multidisciplinary supportive care to optimize the child's growth and development.